1996
DOI: 10.1152/ajpregu.1996.270.6.r1265
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin II and catecholamines in blood pressure variability responses to stress in SHR

Abstract: The contribution of the renin-angiotensin system (RAS) and the sympathetic nervous system (SNS) to blood pressure (BP) and heart rate (HR) variability responses to air-jet stress was assessed in spontaneously hypertensive (SHR) and Wistar-Kyoto (WKY) rats. Activity of the encogenous RAS was suppressed by chronic treatment by a nonpeptide angiotensin II receptor antagonist (Iosartan). The role of alpha 1-adrenoceptor activity was evaluated in rats by acute administration of prazosin. In untreated animals, an ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…This does not occur when the SNS is most active (during the night). Similarly, Gaudet et al [41] have shown that the combination of a 1 -adrenoreceptor and chronic AT 1 -receptor blockade by losartan was more hypotensive compared with the effect of prazosin alone in WKY rats and SHRs. They suggested that the chronic inhibition of the RAS led to increased sympathetic tone [41].…”
Section: Discussionmentioning
confidence: 79%
“…This does not occur when the SNS is most active (during the night). Similarly, Gaudet et al [41] have shown that the combination of a 1 -adrenoreceptor and chronic AT 1 -receptor blockade by losartan was more hypotensive compared with the effect of prazosin alone in WKY rats and SHRs. They suggested that the chronic inhibition of the RAS led to increased sympathetic tone [41].…”
Section: Discussionmentioning
confidence: 79%
“…The reason is twofold. First, effects of air-jet stress on fast rhythms of AP have been thoroughly described in rats (2,4,12). Secondly, an increased sympathetic baroreflex gain is expected to attenuate low and very low frequency components of AP variability (5,15).…”
Section: Discussionmentioning
confidence: 99%
“…Immediately afterward, an additional catheter was inserted into the femoral artery of all animals, as described in ref. 31, for continuously recording arterial BP. The catheters were tunneled s.c. to exit from the neck.…”
Section: Methodsmentioning
confidence: 99%